The Effect of Overconfidence Bias and Herding Bias on Investment Decisions in the Millennial Generation in Surabaya - Dewi Pertiwi; Agus Winata (Jurnal Riset Akuntansi dan Keuangan, 2023)
Millennials who are adaptable are able to see investment opportunities that are easy to do through the world of digital technology. The millennial generation sees investment instruments as an opportunity for future income or income related to passive income which influences their investment decisions. The Covid-19 event has encouraged investors, especially young people, to invest in stock instruments. One of the reasons is that buying and selling shares can be done anywhere, without the need for high mobility. This is shown by the increase in the number of investors who are dominated by the Millennial generation, especially during the pandemic. On the other hand, stock decision making based on limited knowledge has resulted in bias. Generally, novice investors tend to make investment decisions based on emotions compared to available data and information. This research was conducted to examine the effect of Overconfidence Bias and Herding Bias on the investment decisions of the millennial generation in Surabaya. The results of this study indicate that Overconfidence Bias and Herding Bias have a significant effect on the investment decisions of the millennial generation in Surabaya.